Product Diversification of Robusta Coffee Cascara at Gapoktan Karya Bakti: An Effort to Support Zero Waste: Diversifikasi Produk Cascara Kopi Robusta Pada Gapoktan Karya Bakti Sebagai Upaya Mendukung Zero Waste - Riski Ayu Anggreini; Luqman Agung Wicaksono; Tria Puspa Sari; Sri Alam Syah Lihan Candra Asi; Dwi Mulyani (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Gapoktan Karya Bakti is a farmer group in Kenongo Village, Gucialit District, Lumajang Regency, which is able to produce 9.6 tons of robusta coffee annually. To overcome the problem of coffee waste and increase added value for farmers, it is necessary to develop products from cascara. Cascara (coffee skin) has a fairly high antioxidant content so that it has great potential to be used as a new product (diversification of food products). This activity was carried out to provide counseling on the cascara tea making process, handover of drying technology, and packaging label design at Gapoktan Karya Bakti to increase efficiency in cascara processing, help strengthen brand identity, and expand the reach of the cascara tea market. The counseling material is in the form of an explanation related to the cascara tea making process and how to use drying technology in the production process. The results of the community service activities are expected to improve the economy of Gapoktan Karya Bakti members and support the zero waste concept from the utilization of coffee waste.